2022
DOI: 10.1590/1518-8345.5636.3522
|View full text |Cite
|
Sign up to set email alerts
|

Skin injuries due to Personal Protective Equipment and preventive measures in the COVID-19 context: an integrative review

Abstract: Objective to identify the diverse scientific evidence on the types of skin lesions caused due to the use of Personal Protective Equipment in health professionals during the COVID-19 pandemic and to verify the recommended prevention measures. Method this is an integrative review carried out in the MEDLINE, CINAHL, LILACS, SCOPUS, Science Direct, Web of Science and SciELO databases. The search was conducted in a paired manner, constituting a sample of 17 studies categorized according to the types of skin lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
(88 reference statements)
3
5
1
3
Order By: Relevance
“…18 The results of one systematic review in 2022 also showed that masks caused pressure injuries are mainly grade 1. 20 In this regard, the results of Rafiei et al's study, which was conducted among nurses in Qazvin hospitals at the beginning of the COVID-19 pandemic, showed that in addition to grade 1 injuries, a significant percentage of PPE-related pressure injuries are grade 2, which it is different from the findings of the current study. 4 The differences between the two studies can be related to three reasons.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…18 The results of one systematic review in 2022 also showed that masks caused pressure injuries are mainly grade 1. 20 In this regard, the results of Rafiei et al's study, which was conducted among nurses in Qazvin hospitals at the beginning of the COVID-19 pandemic, showed that in addition to grade 1 injuries, a significant percentage of PPE-related pressure injuries are grade 2, which it is different from the findings of the current study. 4 The differences between the two studies can be related to three reasons.…”
Section: Discussioncontrasting
confidence: 93%
“…Similar to this finding, the results of the study conducted in Turkey showed that the PPE‐related pressure injuries in healthcare providers are mostly grade 1 18 . The results of one systematic review in 2022 also showed that masks caused pressure injuries are mainly grade 1 20 . In this regard, the results of Rafiei et al's study, which was conducted among nurses in Qazvin hospitals at the beginning of the COVID‐19 pandemic, showed that in addition to grade 1 injuries, a significant percentage of PPE‐related pressure injuries are grade 2, which it is different from the findings of the current study 4 .…”
Section: Discussionsupporting
confidence: 69%
“…This is consistent with the results of previous studies (Gasparino et al, 2021). A recent comprehensive review (Silva et al, 2022) similarly showed that foam dressings were The prevention of MRDPI by foam dressings can be explained in two ways. First, foam dressings are highly resistant to pressure and shear forces (Graça et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of previous studies (Gasparino et al, 2021). A recent comprehensive review (Silva et al, 2022) similarly showed that foam dressings were effective for preventing skin damage caused by personal protective equipment during the COVID‐19 pandemic. The SUCRA values indicated that foam dressing was the best intervention.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that among the complications caused by glove wearing, dryness (75%) and rash/itching (72.2%) were the main complaints ( 60 ), which was consistent with previous studies by Sliva et al ( 61 ) and Xia et al ( 62 ). In addition, sweating and redness could be also hand symptoms ( 63 ).…”
Section: Contact Dermatitis Caused By Ppe During the Covid-19 Pandemicsupporting
confidence: 87%